IMPLIKASI REVOLUSI INDUSTRI 4.0 TERHADAP PROSES PEMBELAJARAN DI PERGURUAN TINGGI - Abdul Wahab Syakhrani; Iwan Ridwan; Joni Wilson Sitopu (Adiba Aisha Amira, 2024)
The Industrial Revolution 4.0 brings great impact to the learning process in higher education by introducing advanced technologies such as Artificial Intelligence (AI), Augmented Reality (AR), Virtual Reality (VR), and big data. This transformation allows universities to implement more flexible, interactive and efficient learning methods. In addition, the use of these technologies enables curriculum personalisation according to the needs and abilities of individual students, which supports more effective and holistic learning. However, with the deepening integration of technology, there is a challenge for universities to ensure students have the necessary digital literacy, analytical ability, critical thinking and creative skills. Therefore, it is important to adjust the curriculum and develop soft skills so that university graduates are ready to adapt to the demands of the digital era.